Odeminiwin: Understanding and Supporting Childhood Stimulation in an Algonquin Community - Thorne, Rebecca; Macdonald, Mary; Thivierge, Christine; Whiteduck, Georgina; Vignola, Serge (First Peoples Child & Family Review, 2016)
Legacies of colonialism have been associated with risk factors for delayed childhood development in Aboriginal communities in Canada. In the Algonquin community of Rapid Lake (Québec, Canada), the maternal-child nurse carries out regular screening for developmental delay in children (0-66 months) using the Ages and Stages Questionnaire (ASQ). The aim of this project was to explore parenting practices and cultural traditions regarding childhood stimulation in this community as well as primary caregivers’ perceptions of the use of the ASQ. Using a Community Based Participatory Research framework, we conducted a focused ethnography over four months, which included 28 participants. Outcomes of our research included the development of a stimulation activity for families involving all generations in the community, incorporating traditional parenting practices and language, and promoting a safe learning environment. Results can be used to support efforts towards community-driven childhood development services in other Aboriginal communities.